Feuerbach e Marx: estranhamento, fetichismo e emancipação humana - Ariza, Péricles (2019)
The problem of estrangement and fetishism presented by Ludwig Feuerbach in his works, especially his Essence of Christianity (1841) and Lectures on the Essence of Religion (1851), possibly contributed in some way to Marx’s comprehension of the phenomena and fetishistic character of commodity, money, and modern political economy, as well as the understanding of capitalism as a mode of production based on alienated labor, and therefore it has an analogous structure to religion or religious alienation. Thus, the so-called political economy and bourgeois economists, according to Marx, would have done nothing more than establish and idealize a new theology. In fact, the capitalist religion, of the cult of money, has become, in the course of history, more powerful than Christianity itself or any other religion, reigning absolutely over humanity and society. For Marx, Christianity, with its worship of God and the abstract being, is the most useful and adequate religion to capitalism, as well as, in a certain way, responsible for preparing the ground for the subjective and ideological field. After all, Capital as well as God, according to Marx's theory, represents the alienated and externalized essence of man, who is dominated and worshiped by him. Religious fetishism or religious alienation, in transforming the creature into creator, inverts the world and all its values, turning things into men and men into things, that is, it begins a process of objectification and the humanization of things. The historical drama lived by humanity today is the drama of fetishism. Just as in religious fetishism or religious idolatry, capitalist fetishism, sustained and stimulated by the ruling class, acts as an instrument of domination and legitimation of structures of oppression and exploitation of man by man. Like Feuerbach, Marx also seeks to denounce the blockade of progress, culture and human emancipation, created by alienation and fetishism or religious idolatry. For both Marx and Feuerbach, human emancipation, and thus the overcoming of fetishism by humanity, must pass through philosophy as well as the proletariat.